NRC celebrates 20 years of service to the care home sector. (2nd April 2019) - Allen, Mark; Ashurst, Adrian; Cook, Glenda; Harrison-Dening, Karen; Hong, Chia Swee; Johnson, Karen; Swann, Julie
Abstract : This month sees the 20 th anniversary of Nursing and Residential Care . Mark Allen, the Chairman of the Mark Allen Group and members of the NRC editorial board look back at how the care home sector and the journal have evolved over the years.